2023
DOI: 10.1111/1365-2664.14382
|View full text |Cite
|
Sign up to set email alerts
|

Environmental context and herbivore traits mediate the strength of associational effects in a meta‐analysis of crop diversity

Abstract: Crop diversification offers a promising solution to meet expanding global food demands while maintaining ecosystem services. Diversification strategies that use mixed planting to reduce pest damage (e.g. intercropping), termed ‘associational effects’ (AE) in the ecological literature, can decrease (associational resistance) or increase (associational susceptibility) herbivore abundance on a focal plant. While application of AE to agroecosystems typically reduces pest abundance, the range of outcomes varies wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Thus, these findings suggest that less dense plants benefit by escaping host detection in LPRs whereas host plant detection seems similar regardless of density in the HPR. Although plant diversity might differ between LRR and HRR, evidence shows that most specialist herbivores are unlikely to be strongly influenced by heterospecific neighbors (Hahn & Cammarano, 2023 ). In sum, our results suggest that densities of host plant resources (seed heads per plant) for specialist herbivores, potentially in addition to other factors such as the overall population size, spatial distribution, and herbivore abundance are important for predicting herbivory levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these findings suggest that less dense plants benefit by escaping host detection in LPRs whereas host plant detection seems similar regardless of density in the HPR. Although plant diversity might differ between LRR and HRR, evidence shows that most specialist herbivores are unlikely to be strongly influenced by heterospecific neighbors (Hahn & Cammarano, 2023 ). In sum, our results suggest that densities of host plant resources (seed heads per plant) for specialist herbivores, potentially in addition to other factors such as the overall population size, spatial distribution, and herbivore abundance are important for predicting herbivory levels.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that increasing the biodiversity of agroecosystems through intercropping can increase overall agricultural yields (Chai et al 2021; Li et al 2021b; Li et al 2023) by increasing nutrient acquisition (Li et al 2014) and reducing pest pressure (Trenbath 1993;Poveda et al 2008). Diversi cation of agroecosystems through intercropping generally reduces herbivore and pathogen density, however the size and direction of these effects varies substantially between studies and systems (Letourneau et al 2011; Chad eld et al 2022; Hahn and Cammarano 2023). Intercropping could in uence resistance to pests and pathogens through at least several hypothesized mechanisms, such as numerical dilution of host plants (and host plant cues) (Tahvanainen and Root 1972;Root 1973), disruption of insect host-nding by non-host cues, increased accumulation of natural enemies like predators and parasitoids, or resistance-enhancing changes in the metabolism of the focal plant species (Poveda et al 2008; Barbosa et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, among natural enemies, predators often have wider diet breadths than parasitoids, which must evolve strategies to overcome host prey defenses and thus often specialize within a genus or family of prey ( Vorburger 2022 ). A recent global meta-analysis found that the decline of generalist herbivore abundance in response to crop resource dilution in bicultures was stronger than the decline in specialist herbivore abundance ( Hahn and Cammarano, 2023 ), and numerous other studies have observed variable responses to landscape-level resource concentration among herbivores and natural enemies with varying diet breadths ( Egerer et al, 2017 ; Perez-Alvarez et al, 2019 ). While general patterns emerge from a global perspective, regional variation in arthropod responses to local and landscape-level resource availability underscores the need for regional and crop-specific studies to understand herbivory risks within a given production system.…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies of biocontrol by natural enemies in Ohio Cucurbita production found that predators were not influenced by the availability of alternative host plants and that control of target specialist herbivores was higher in sites with greater predator richness and in landscapes with more agriculture ( Phillips and Gardiner, 2016 ; Mabin et al, 2020 ). These and an additional three studies ( Lawrence and Bach 1989 ; Hooks et al, 1998 , and Frank and Liburd, 2005 ) included in a recent meta-analysis ( Hahn and Cammarano, 2023 ) all utilized additive polycultures to examine variation in the relative density of Cucurbita plants and test the Resource Concentration Hypothesis as a frequency-dependent process ( Kim and Underwood, 2015 ). Much less is known about how absolute density-dependent processes, derived from variation in local-level Cucurbita establishment and landscape-level Cucurbita production, influence herbivory.…”
Section: Introductionmentioning
confidence: 99%